2014
DOI: 10.1162/rest_a_00348
|View full text |Cite
|
Sign up to set email alerts
|

Employment Protection Legislation, Multinational Firms, and Innovation

Abstract: The theoretical effects of labour regulations such as employment protection legislation (EPL) on innovation is ambiguous, and empirical evidence has thus far been inconclusive. EPL increases job security and the greater enforceability of job contracts may increase worker investment in innovative activity. On the other hand EPL increases adjustment costs faced by firms, and this may lead to under-investment in activities that are likely to require adjustment, including technologically advanced innovation. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 43 publications
5
55
0
4
Order By: Relevance
“…Similarly, greater employment protection may encourage firms to invest in firm-specific human capital that benefits productivity (Autor, 2003;Wasmer, 2006). Griffith and Macartney (2010) find that multinational firms do more patenting of incremental innovations in relatively high EPL countries and more patenting of radical innovations in low EPL countries. Such heterogeneous effects indicate that it may be difficult to identify the impact of a change in EPL on R&D http://www.rei.unipg.it/rei/article/view/128 11 expenditure or patenting in a cross-country study based on aggregate data.…”
Section: Framework Policiesmentioning
confidence: 80%
“…Similarly, greater employment protection may encourage firms to invest in firm-specific human capital that benefits productivity (Autor, 2003;Wasmer, 2006). Griffith and Macartney (2010) find that multinational firms do more patenting of incremental innovations in relatively high EPL countries and more patenting of radical innovations in low EPL countries. Such heterogeneous effects indicate that it may be difficult to identify the impact of a change in EPL on R&D http://www.rei.unipg.it/rei/article/view/128 11 expenditure or patenting in a cross-country study based on aggregate data.…”
Section: Framework Policiesmentioning
confidence: 80%
“…This explains why, for instance, countries with stringent EPL tend to have smaller ICT intensive sectors (see Bartelsman et al, 2010), an observation confirmed by recent OECD empirical evidence showing that "higher EPL lowers productivity growth by handicapping firms that operate in environment subject to greater technological change" (Andrews and Criscuolo, 2013). Furthermore, there is also evidence showing that multinational firms tend to concentrate their more radical and disruptive innovative activities in countries with low EPL where resource reallocation is easier (Griffith and Macartney, 2014).…”
Section: Labour Market Regulationmentioning
confidence: 90%
“…The effects of EPL on innovation are however more ambiguous than the discussion so far may suggest, although empirical evidence for the beneficial effects of stringent EPL on innovation is still rather scarce (see Andrews and Criscuolo, 2013;Griffith and Macartney, 2014). EPL increases job security, and the greater enforceability of job contracts can increase worker investment in innovative activity.…”
Section: Labour Market Regulationmentioning
confidence: 99%
“…On the one hand, the Danish-type flexicurity with relatively weak employment protection but relatively high unemployment benefits might be particularly conducive for start-up formation and radical innovation but, on the other hand, weak employment protection may deteriorate employees' incentives to innovate in established corporations (see, e.g., , Bozkaya and Kerr, 2013, and Griffith and Macartney, 2014 for different results).…”
Section: Other Indirect Innovation Policiesmentioning
confidence: 99%